2015
DOI: 10.1186/s10194-015-0547-z
|View full text |Cite
|
Sign up to set email alerts
|

Migraine is associated with an increased risk for benign paroxysmal positional vertigo: a nationwide population-based study

Abstract: BackgroundThere is evidence suggesting that migraine may be associated with vertigo. The aim of this study was to assess the risk of benign paroxysmal positional vertigo (BPPV), the most common form of vertigo, in patients with migraine using a population-based dataset.MethodsThe National Health Insurance Research Database in Taiwan was searched for migraine patients and was also used to select an age- and sex-matched cohort of subjects without migraine. The analyses included 8266 migraine patients and 8266 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
(28 reference statements)
1
34
1
5
Order By: Relevance
“…Previous studies have shown that patients with migraine seem more likely to develop BPPV than subjects in the control group. [7][8][9] Kim et al 10 performed a nationwide cohort study and reported a higher incidence of BPPV in patients with migraine (6.0%) than in control subjects (3.2%). Faralli et al 11 reviewed the recovery time, residual dizziness, and recurrence in patients with BPPV with and without migraine.…”
Section: Migrainementioning
confidence: 99%
“…Previous studies have shown that patients with migraine seem more likely to develop BPPV than subjects in the control group. [7][8][9] Kim et al 10 performed a nationwide cohort study and reported a higher incidence of BPPV in patients with migraine (6.0%) than in control subjects (3.2%). Faralli et al 11 reviewed the recovery time, residual dizziness, and recurrence in patients with BPPV with and without migraine.…”
Section: Migrainementioning
confidence: 99%
“…Also, patients can have headache with their BPV [83] and those who have migraine are more likely to have BPV than those who do not [84]; those who have idiopathic BPV are more likely also to have migraine than those who have post-traumatic BPV [85]. …”
Section: Vestibular Migrainementioning
confidence: 99%
“…27 mostly if migraineurs aged ≥40 years(HR = 2.20). 28 Moreover, compared to Meniere's disease group, patients with benign recurrent vertigo (BRV) had a female preponderance, earlier age of onset, and increased incidence of migraine (OR = 0.3). 29 These findings were confirmed by Porta-Etessam and coll., assuming that migraine associated recurrent vertigo (MARV) and the possible vestibular hypofunction of migraine patients are symptoms that share physiological aspects with migraine.…”
Section: Discussionmentioning
confidence: 99%